Scope innovative management system (SC) - Selvi, Rangasamy (2014)
The demands of technology and the global economy make it important that individuals of all ages have access to affordable education. Scope Innovative plays a vital role to help students to provide extra knowledge that apart from the education. Scope Innovative management system (SC) not applying of Information technology into the system for reducing the workload. SC is using manual filling for notation and reporting. This SC is developing due to lack of computerized in management system for SC. The review had been made to compare the inefficiency of existing system with current system. This system has the ability to keep abundant data in organized, and reduce the uses of papers. The users of this system are staffs of the centre, tutors, cashier and admin. The uses of database element can produce more structured system data. SC center management system will be developed using the web-based system and a kind of client-server environment. Rapid Application Development has been chosen as the method to develop this system. The phases are requirement planning, user design, construction and cutover. This methodology is chosen because it attempts to reduce inherent project risk by breaking a project into smaller segments, provides easy to change during the development process and it is suitable for developing SC. PHP, JavaScript and HTML language are used to develop this system and xampp Server will be used for database as well. Thus, this system helps to enhance and standardize SC management.